Recent Advances on the Structure and Function of RNA Acetyltransferase Kre33/NAT10 - Sleiman, Sophie (Cells, 2019)
Ribosome biogenesis is one of the most energy demanding processes in the cell. In eukaryotes, the main steps of this process occur in the nucleolus and include pre-ribosomal RNA (pre-rRNA) processing, post-transcriptional modifications, and assembly of many non-ribosomal factors and ribosomal proteins in order to form mature and functional ribosomes. In yeast and humans, the nucleolar RNA acetyltransferase Kre33/NAT10 participates in different maturation events, such as acetylation and processing of 18S rRNA, and assembly of the 40S ribosomal subunit. Here, we review the structural and functional features of Kre33/NAT10 RNA acetyltransferase, and we underscore the importance of this enzyme in ribosome biogenesis, as well as in acetylation of non-ribosomal targets. We also report on the role of human NAT10 in Hutchinson–Gilford progeria syndrome.